Precision measurement of the ratio B(t→Wb)/B(t→Wq) and extraction of Vtb - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Arov, M.; et al. (American Physical Society (APS), 2011)
We present a measurement of the ratio of top quark branching fractions R=B(t→Wb)/B(t→Wq), where q can be a d, s, or b quark, in the lepton+jets and dilepton tt̄ final states. The measurement uses data from 5.4fb-1 of pp̄ collisions collected with the D0 detector at the Fermilab Tevatron Collider. We measure R=0.90±0.04, and we extract the Cabibbo-Kobayashi-Maskawa (CKM) matrix element |Vtb| as |V tb|=0.95±0.02, assuming unitarity of the 3×3 CKM matrix. © 2011 American Physical Society.